2014
DOI: 10.4049/jimmunol.1301297
|View full text |Cite
|
Sign up to set email alerts
|

Gap Junction Intercellular Communications Regulate NK Cell Activation and Modulate NK Cytotoxic Capacity

Abstract: Gap junctions (GJs) mediate intercellular communication between adjacent cells. Previously, we showed that connexin 43 (Cx43), the main GJ protein in the immune system, mediates Ag transfer between human dendritic cells (DCs) and is recruited to the immunological synapse during T cell priming. This crosstalk contributed to T cell activation, intracellular Ca2+ responses, and cytokine release. However, the role of GJs in NK cell activation by DCs and NK cell–mediated cytotoxicity against tumor cells remains unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 47 publications
2
60
0
Order By: Relevance
“…Ectopic Overexpression of Cx43 Enhances NK-mediated Tumor Cell Killing by Stabilizing the Immune Synapse-It has been reported that the inhibition of Cx43 channels strongly decreased NK-mediated tumor cell lysis (10). In keeping with this, we investigated whether the overexpression of Cx43 in the M4T melanoma cell model influences their susceptibility to NK cell-mediated lysis.…”
Section: Hypoxia Increases the Expression Of Cx43 In Melanoma Cells Vmentioning
confidence: 90%
See 3 more Smart Citations
“…Ectopic Overexpression of Cx43 Enhances NK-mediated Tumor Cell Killing by Stabilizing the Immune Synapse-It has been reported that the inhibition of Cx43 channels strongly decreased NK-mediated tumor cell lysis (10). In keeping with this, we investigated whether the overexpression of Cx43 in the M4T melanoma cell model influences their susceptibility to NK cell-mediated lysis.…”
Section: Hypoxia Increases the Expression Of Cx43 In Melanoma Cells Vmentioning
confidence: 90%
“…Autophagy was inhibited by addition of 50 M hydroxychloroquine (HCQ) or 5 mM 3-methyladenine (both from Sigma-Aldrich). Cx43 channels were inhibited using Cx43-mimetic peptides (300 M, gap27, SRPTEKTIFII, Synprosis) (10,24). A scrambled peptide (TFEPIRISITK) was used as a control.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NKT cells string together characteristics of innate and adaptive immunity [150], reviewed in [151]: they activate receptors and express inhibiting receptors that sense the presence of the MHC class I molecules expressed on all healthy cells [152], reviewed in [151]. Cx43 regulates NKT activation: knockdown reduced CD69 and CD25 expression and also the IFN-γ secretion usually released by NKT induced through human dendritic cells and blocking the Cx43-suppressed NKT-mediated tumor cell lysis [153]. The αv-containing Integrins are known to be essential for fibrosis [154], a pharmacological blockade of the αv-subunit has been shown to attenuate liver and lung fibrosis in mice treated with a novel small molecule, (CWHM 12) [155].…”
Section: (2) Cell-cell Communication In Microenvironment and Carcinogmentioning
confidence: 99%